2004
DOI: 10.1081/jdi-120038522
|View full text |Cite
|
Sign up to set email alerts
|

Renal Sodium Handling Study in an Atypical Case of Bartter's Syndrome Associated with Mitochondriopathy and Sensorineural Blindness

Abstract: Bartter's syndrome is a disorder that has been linked to mutations in one of three ion transporter proteins: NKCC2 (type I), ROMK (type II) and CCLNKB (type III), which affects a final common pathway that participates in ion transport by thick ascending limb cells. We present an atypical case of mitochondriopathy combined with tubule functional disturbances compatible with Bartter's syndrome and definitive sensorineural blindness. Our patient had a peculiar clinical presentation with signs of salt and volume d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Notably, no other organs were affected in these four patients; thus, kidney disease was the initial manifestation and dominant feature of the MID and, therefore, the phenotype was not consistent with MELAS syndrome at the time of diagnosis (63). In a patient with sensorineural blindness, attributed to a non-genetically proven MID, Bartter-like syndrome was the second phenotypic feature (64). In a consanguineous family with isolated COX-deficiency due to a mutation in the COX10 gene, which encodes the heme A:farnesyltransferase, increased urinary amino acids suggested proximal renal tubulopathy (65).…”
Section: Mdsmentioning
confidence: 99%
“…Notably, no other organs were affected in these four patients; thus, kidney disease was the initial manifestation and dominant feature of the MID and, therefore, the phenotype was not consistent with MELAS syndrome at the time of diagnosis (63). In a patient with sensorineural blindness, attributed to a non-genetically proven MID, Bartter-like syndrome was the second phenotypic feature (64). In a consanguineous family with isolated COX-deficiency due to a mutation in the COX10 gene, which encodes the heme A:farnesyltransferase, increased urinary amino acids suggested proximal renal tubulopathy (65).…”
Section: Mdsmentioning
confidence: 99%
“…Further arguments for a non-syndromic MtD are that hypokalemia or hyperaldosteronism has been previously reported as clinical manifestations of MtD (Goto et al 1990;Harvey and Barnett 1992;Wang et al 2000;Menegon et al 2004;Park et al 2004;Emma et al 2006). Emma et al (2006) reported a 14-year-old patient with KSS who developed Bartter's syndrome (hyper-reninemic hyperaldosteronism).…”
Section: Discussionmentioning
confidence: 99%
“…Hyper aldosteronism was reported as one among various other phenotypic features in a single male with KSS (Mihai et al 2009). Menegon et al (2004) described a patient with atypical Bartter's syndrome and MtD who presented with salt and volume depletion, hypotonia, and secondary hyperaldosteronism associated with hypokalemic metabolic alkalosis, hypocalcaemia and severe hypomagnaesemia. These abnormalities were attributed to mitochondrial dysfunction within the epithelium of the ascending loop of Henle (Menegon et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations